Efficacy of Magnesium Trihydrate of Ursodeoxycholic Acid and Chenodeoxycholic Acid for Gallstone Dissolution: A Prospective Multicenter Trial - Hyun, Jong Jin; Lee, Hong Sik; Kim, Chang Duck; Dong, Seok Ho; Lee, Seung-Ok; Ryu, Ji Kon; Lee, Don Haeng; Jeong, Seok; Kim, Tae Nyeun; Lee, Jin; Koh, Dong Hee; Park, Eun Taek; et al. (Gut and Liver, 2015)
Cholecystectomy is necessary for the treatment of symptomatic or complicated gallbladder (GB) stones, but oral litholysis with bile acids is an attractive alternative therapeutic option for asymptomatic or mildly symptomatic patients. This study was conducted to evaluate the efficacy of magnesium trihydrate of ursodeoxycholic acid (UDCA) and chenodeoxycholic acid (CDCA) on gallstone dissolution and to investigate improvements in gallstone-related symptoms. A prospective, multicenter, phase 4 clinical study to determine the efficacy of orally administered magnesium trihydrate of UDCA and CDCA was performed from January 2011 to June 2013. The inclusion criteria were GB stone diameter ≤15 mm, GB ejection fraction ≥50%, radiolucency on plain X-ray, and asymptomatic/mildly symptomatic patients. The patients were prescribed one capsule of magnesium trihydrate of UDCA and CDCA at breakfast and two capsules at bedtime for 6 months. The dissolution rate, response rate, and change in symptom score were evaluated. A total of 237 subjects were enrolled, and 195 subjects completed the treatment. The dissolution rate was 45.1% and the response rate was 47.2% (92/195) after 6 months of administration of magnesium trihydrate of UDCA and CDCA. Only the stone diameter was significantly associated with the response rate. Both the symptom score and the number of patients with symptoms significantly decreased regardless of stone dissolution. Adverse events necessitating discontinuation of the drug, surgery, or endoscopic management occurred in 2.5% (6/237) of patients. Magnesium trihydrate of UDCA and CDCA is a well-tolerated bile acid that showed similar efficacy for gallstone dissolution and improvement of gallstone-related symptoms as that shown in previous studies.